Species composition of anopheles mosquitoes in Danum Valley, Lahad Datu, Sabah. - Sonia Hui Meng Ling; Homathevi Rahman; Sylvia Daim; Hairul Hafiz Mahsol; Benny Obrain Manin; Clarissa Patrick Balinu; Kimberly Fornace; Tock Hing Chua (Universiti Malaysia Sabah, 2024)
Malaria continues to be a public health concern globally, while in Malaysia, cases remain high among interior communities in Borneo, including in Sabah. We studied the Anopheles species in Danum Valley, Lahad Datu, by random sampling of mosquitoes in the virgin forest of the Danum Valley Conservation Area (VF), low-ground regenerated forest (100m above sea level) (LRF) and high-ground regenerated forest (400m above sea level) (HRF). Over 12 trap nights, a total of 839 individuals of Anopheles mosquitoes belonging to nine species were collected with mosquito magnet: Anopheles asiaticus (94), An. balabacensis (12), An. barbumbrosus (7), An. fragilis (640), An. interruptus (38), An. jamesii (9), An. latens (5), An. maculatus (17) and An. montanus (17). Among them, are vectors for zoonotic malaria in Malaysia namely Anopheles balabacensis (1.43%), An. maculatus (2.03%) and An. latens (0.60%), albeit relatively low in numbers. HRF had the highest number of Anopheles mosquitoes collected (670), followed by LRF (130) and VF (39). Both Simpson’s (D) and Shannon-Wiener (H) diversity indices were highest at LRF (D = 2.07; H = 1.2 with highest Species Evenness, E = 0.58), followed by HRF (D = 1.62; H = 0.8; E = 0.39) and VF (D = 1.31; H = 0.47; E = 0.43. Greater numbers of the malaria vectors were found in LRF and HRF, compared to VF suggesting that there may be greater exposure to vectors and vector-associated diseases when entering these regenerated forests. Significant differences (p < 0.05) for different forest types were detected for the total number of mosquitoes, total Anopheles and An. fragilis between different forest types.